Orimeten v lécbĕ pokrocilého karcinomu prostaty - Vachalovský, V; Vomácka, V (Rozhledy v chirurgii, 1989)
The authors treated 16 patients with advanced prostate carcinoma after previous orchiectomy and further progression of the disease: 9 patients with Cyclophosphamide + Ftorafur + placebo and seven patients with Cyclophosphamide + Ftorafur + Orimeten. They achieved in particular improvement of the subjective complaints, while in both groups there was objective progression of the disease. In the group with Orimeten the objective progression of the disease was slower than in the group where cytostatics alone were administered.
Keywords: senioři; aminoglutethimid; ftorafur; cyklofosfamid; senioři nad 80 let; Aminoglutethimide; Drug Therapy, Combination; Middle Aged; mužské pohlaví; nádory prostaty; Tegafur; Antineoplastic Agents; Carcinoma; Aged, 80 and over; kombinovaná farmakoterapie; protinádorové látky; Cyclophosphamide; Humans; Prostatic Neoplasms; lidé středního věku; Aged; lidé; Male; karcinom